A Stochastic Convergence Result for the Nelder–Mead Simplex Method - Aurél Galántai (Mathematics, 2023)
We prove that the Nelder–Mead simplex method converges in the sense that the simplex vertices converge to a common limit point with a probability of one. The result may explain the practical usefulness of the Nelder–Mead method.